Substance use and mental health characteristics among pregnant individuals with medical and non-medical benzodiazepine use early in pregnancy - Ayesha C. Sujan; Natalie E. Slama; Brian T. Bateman; Deborah Ansley; Carley Castellanos; Kelly C. Young-Wolff (Drug and Alcohol Dependence Reports)
Background: Research to date evaluating the safety of benzodizapine use during pregnancy has shown mixed results and has relied on self-report or filled prescription data, which are unlikely to capture non-medical use and, consequently, could bias results. Therefore, research on non-medical benzodiazepine use during pregnancy is needed. Methods: The present study used data from a large, healthcare system with universal screening for prenatal substance use via urine toxicology tests and information on filled prescriptions. We first evaluated the prevalence of pregnancies with non-medical benzodiazepine use (positive urine toxicology test and no filled prescriptions in the past year) and medical benzodiazepine use (positive urine toxicology test and >1 filled prescription in the past year). We also evaluated the presence of co-occurrence of substance use and mental health conditions among these pregnancies. Results: Our results showed that benzodiazepine use during early pregnancy was rare (<1 % had a positive toxicology test). However, more than one-third of those with a positive toxicology test did not have a filled prescription (i.e., had non-medical use) We also found similar rates of substance use and mental health conditions among pregnancies with medical and non-medical benzodiazepine use. Conclusion: Our results suggest that research relying on prescription data alone and the medical system may be missing pregnant individuals using benzodiazepines. This points to a need for additional measures and screenings (e.g., urine toxicology tests) in both research and clinical settings. Our findings also underscore a need for additional services for pregnant individuals with both medical and non-medical benzodiazepine use.